2019
DOI: 10.1002/htj.21594
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation analysis of natural convective chemically reacting squeezing flow of Casson fluid between parallel disks with Hall and Ion slip currents

Abstract: This paper concerns the second law analysis of free convective squeezing flow of a chemically reacting Casson fluid confined between two parallel disks with Hall and Ion slip effects. The upper one is impermeable and the lower disk is porous. The linear momentum, energy balance and mass partial differential equations converted as system of ODEs by similarity transformations and tackled with shooting method via fourth order Runge-Kutta scheme. The impact of various dimensionless geometric and fluid parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Shah et al [17] defned the fow of micropolar nanofuid in presence of thermally radiative rotating disks for investigation of mass fux and heat fux. Few more related studies on the said topic can be found from the references [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al [17] defned the fow of micropolar nanofuid in presence of thermally radiative rotating disks for investigation of mass fux and heat fux. Few more related studies on the said topic can be found from the references [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%